AN AUTOPSY STUDY OF SUDDEN NATURAL DEATHS IN VICTORIA HOSPITAL, BOWRING AND LADY CURZON HOSPITALS ATTACHED TO BANGALORE MEDICAL COLLEGE, BANGALORE (Journal of Forensic Medicine & Toxicology, 2012)
Sudden deaths are mostly natural deaths which occur immediately or within 24hours of the onset of terminal symptoms, which may be totally different from the symptoms which the patient was having so long. Such cases pose medico legal problems to relatives/ friends/police officers/judiciary/doctors and other law enforcing agencies.
Keywords: Sudden natural death; Autopsy; Medico legal problems; Coronary vessels